Tesis de maestria en Docencia de la Química - Galvis Ferrucho, Willian; Castro Moreno, Julio Alejandro; Trujillo Campos, Alfonso Raúl; Rueda Velázquez, Dora Almáriz; Amador Montaño, José Francisco (Tecné, Episteme y Didaxis: TED, 2007)
Tesis de maestrias de los estudianyes graduados.